The development of an integrated problem-based learning (PBL) approach in a post-matriculation programme at the University of Stellenbosch - Malan, Sharon Brenda (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Educational Psychology))--Stellenbosch University, 2008.